Short communication: Concentrate supplementation strategies in ryegrass pasture for productive performance in lambs - Santos, Sthefany K.; Falbo, Margarete K.; Sandini, Itacir E.; Pacentchuk, Fabiano; Neumann, Mikael; Garbossa, Gabriela (Spanish Journal of Agricultural Research, 2018)
This study evaluated the effect of two concentrate supplementation strategies on performance, metabolic profile and economic evaluation of suckling lambs and ewes in ryegrass (Lolium multiflorum) pasture. Twenty-seven ewes and 45 lambs were divided into three groups: (1) ryegrass pasture without supplementation - control (CON); (2) CON plus supplemented ewes and lambs at 1% of live weight (SEL), and (3) CON plus creep feeding supplemented lambs at 1% of live weight (CSL). Concentrate use increased (p<0.05) average daily gain (ADG) by 19.95% over CON (21.6 and 18.3% for SEL and CSL, respectively). Concentrate use contributed to minimizing forage quality fluctuation and provided greater ADG stability, mainly when ryegrass nutritional content and digestibility decreased. Blood metabolites profiles did not differ between groups, with exception of phosphorus which was higher for CON than SEL, and calcium which was higher for CSL than CON (p<0.05). Compared to CON, stoking rate values were greater to SEL (p<0.05). Compared to CSL, ewe and total stocking rate were greater (p<0.05) to SEL. Considering the control group as break even feed investment, SEL strategy had a positive economic return, while CSL showed economic losses. Concentrate use increased ADG of lambs and decrease the impact of nutrient quality changes of forage on daily gains, but must be considered that supplemental strategy used could affect negatively economic return.